2011
DOI: 10.1017/s0033291711000031
|View full text |Cite
|
Sign up to set email alerts
|

Emotional face processing and flat affect in schizophrenia: functional and structural neural correlates

Abstract: These results suggest that many of the brain regions involved in emotional face perception, including the amygdala, are equally recruited in both schizophrenia and controls, but flat affect can also moderate activity in some other brain regions, notably in the left amygdala and parahippocampal gyrus bilaterally. There were no significant group differences in the volume of the amygdala.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 43 publications
3
26
1
Order By: Relevance
“…As such, the association of negative symptoms with laterality is unclear or perhaps associations exist related to specific negative symptoms. For example, our group identified in FEP patients a significant correlation between higher social withdrawal ratings and reduced parahippocampal grey matter consistently on the right side [80], [81] whereas, in people with chronic schizophrenia, we revealed a significant positive correlation between flat affect ratings and parahippocampal activity bilaterally [82]. Although these studies did not explicitly investigate primary negative symptoms, a neurobiological association may exist with specific negative symptoms that was not explored in the abovementioned studies.…”
Section: Discussionmentioning
confidence: 75%
“…As such, the association of negative symptoms with laterality is unclear or perhaps associations exist related to specific negative symptoms. For example, our group identified in FEP patients a significant correlation between higher social withdrawal ratings and reduced parahippocampal grey matter consistently on the right side [80], [81] whereas, in people with chronic schizophrenia, we revealed a significant positive correlation between flat affect ratings and parahippocampal activity bilaterally [82]. Although these studies did not explicitly investigate primary negative symptoms, a neurobiological association may exist with specific negative symptoms that was not explored in the abovementioned studies.…”
Section: Discussionmentioning
confidence: 75%
“…It has also been reported that these patients show reduced activation or connectivity in the amygdala and parahippocampus during emotion processing [104][105][106] . The nature of this association may be related to the involvement of the amygdala and parahippocampus in managing emotion.…”
Section: Relationship Between Rsfc and Behaviormentioning
confidence: 77%
“…Fusiform gyrus is especially activated by the sight of faces (Taylor et al, 2012). Thus the hypoactivation of fusiform gyrus suggests impairment in processing of perceived visual stimuli in schizophrenia (Lepage et al, 2011; Seiferth et al, 2009). …”
Section: Discussionmentioning
confidence: 99%